Trabalho, subjetividade e gênero: o caso das entregadoras de aplicativos em João Pessoa - Ciraulo, Lizandra Monteiro (2023)
The process of globalization, expansion of informal markets and intensive use of various technologies contributes to the precariousness of female labor and also to its invisibility and lack of social prestige. The professional category chosen in this study was women who work as couriers through a delivery app. Initially, a literature review was carried out, which sought to contextualize the emergence of platform work, with emphasis on the inclusion of women in this work activity. The present study is theoretically based on the Psychodynamics of work and studies on the sexual division of labor. It aims to analyze the relationship between work, subjectivity and gender in the activity of couriers using a delivery app in the city of João Pessoa. A qualitative approach was used, whose main means of data production was the semi-structured individual interview. For data analysis, thematic content analysis proposed by Laville & Dionne (1999) was used. As a result, it is clear that app couriers experience a situation of insecurity, harassment, discrimination and invisibility at work, in addition to long working hours, poor pay and lack of labor rights. It was possible to verify that, due to gender, situations of insecurity increase, harassment and discrimination have a different content, making women suffer even more from invisibilization. In this sense, this activity, while providing some pleasures, produces suffering, arising from the various challenges faced daily. Finally, it is concluded that it is important to bring more visibility to this professional category by presenting proposals for improving their living and working conditions.